Extracellular Proteome Analysis and Flavor Formation During Soy Sauce Fermentation - Zhao, Guozhong; Ding, Li-Li; Yao, Yunping; Cao, Yanping; Pan, Zhi-Hui; Kong, De-Hua (Frontiers in Microbiology, 2018)
Aspergillus oryzae is an excellent strain for soy sauce fermentation because of its complicated enzyme system, especially protease. The aim of this study was to investigate the key enzymes and flavors during soy sauce fermentation, and a comparative assessment of extracellular enzymes during various fermentation stages at the proteomic level via iTRAQ analysis is presented. Many important enzymes related to the amino acid and glucose metabolisms participated in the material decomposition under high-salt stress. Dipeptidase, dipeptidyl aminopeptidase, leucine aminopeptidase, aspartic protease pep1, and extracellular metalloproteinase played positive roles during the early stage of soybean mash fermentation, whilst leucine aminopeptidase A and extracellular metalloproteinase NpI were the dominant proteolytic enzymes during the later period of fermentation. At the same time, β-glucosidase and β-xylanase exerted great effects upon glucose metabolism throughout the fermentation process. The results show that protease and amylolytic enzymes are complementary in the formation of flavors such as alcohols, acids, esters, aldehydes, furans, and pyrazines during soy sauce fermentation.